A participação dos catadores na política de gestão de resíduos sólidos urbanos em Porto Alegre: avanços e limites - Pinheiro, Simone Poças (Universidade do Vale do Rio dos Sinos, 2022)
In Porto Alegre, environmental problems have worsened in recent years, especially in the issue involving urban solid waste, which impact the lives of the population in general and the collectors of solid recyclable materials. The Social Sciences are part of this environment as the understanding that environmental problems arise as a result of economic and social organization. Therefore, the collectors of solid recyclable materials in Porto Alegre are social actors that are inserted in the recycling chain, and aim at a more effective participation in the Management of Solid Urban Waste in Porto Alegre. Because they are the ones who work the most in this process and the ones who have the lowest remuneration. The research proposes to investigate the reasons why, after twelve years of validity of the National Solid Waste Policy (PNRS), the collectors are still in such a precarious social, political and economic situation and their participation in the Solid Urban Waste Management in Porto Joyful so expressionless. The general objective is to analyze the processes of participation of waste pickers in Porto Alegre in the Management of Solid Urban Waste, understanding the constraints of advances and limits in their decision-making capacity. The methodology used was a documentary and bibliographic research, for a qualitative approach, groups focal points with the collectors and semi-structured interviews, which were also carried out with public servants and representatives of the private sector. The study concludes that there is a scenario of dispute of economic interests, as solid waste starts to have financial value. It becomes a market to be disputed, with the entry of private companies and a reduction in the participation of collectors in the Solid Urban Waste Management Policy in Porto Alegre. A support network from different levels of society is necessary for the collectors, initially in the Associations/Cooperatives, passing through their representative spheres, thus seeking a new form of effective participation in the Municipal Solid Waste Management Policies of the municipality and also the other social actors involved. Each one assuming their responsibilities, articulating with the collectors and not leaving them on the sidelines of this process.
Keywords: Participação; Catadores; Resíduos sólidos urbanos; Participation; Collectors; Urban solid waste; ACCNPQ::Ciências Humanas::Sociologia